2021
DOI: 10.1021/jacs.1c00384
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Highly Active Ru Sites by Suppressing Lattice Oxygen Participation in Acidic Water Oxidation

Abstract: In hydrogen production, the anodic oxygen evolution reaction (OER) limits the energy conversion efficiency and also impacts stability in proton-exchange membrane water electrolyzers. Widely used Ir-based catalysts suffer from insufficient activity, while more active Ru-based catalysts tend to dissolve under OER conditions. This has been associated with the participation of lattice oxygen (lattice oxygen oxidation mechanism (LOM)), which may lead to the collapse of the crystal structure and accelerate the leach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
250
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(301 citation statements)
references
References 41 publications
7
250
0
3
Order By: Relevance
“…S11†). What is even more remarkable is that among the most recent ruthenium-based acidic OER electrocatalysts reported in 2021 (Table 1), 44–49 In 0.17 Ru 0.83 O 2 -350 has the highest mass activity (1094.90 A g Ru −1 @ η = 300 mV) and the lowest Tafel slope of 32.62 mV dec −1 (Fig. 3b, S12 and Table S5†).…”
Section: Resultsmentioning
confidence: 93%
“…S11†). What is even more remarkable is that among the most recent ruthenium-based acidic OER electrocatalysts reported in 2021 (Table 1), 44–49 In 0.17 Ru 0.83 O 2 -350 has the highest mass activity (1094.90 A g Ru −1 @ η = 300 mV) and the lowest Tafel slope of 32.62 mV dec −1 (Fig. 3b, S12 and Table S5†).…”
Section: Resultsmentioning
confidence: 93%
“…Note that LOER is al attice oxygen oxidation process involving direct O-O coupling and the formation of ahighly active oxyhydroxide surface layer, which is critical for the structural evolution triggered by electrode imbalance.I n addition to the activity,the regulation of surface evolution is demonstrated as an efficient approach to improve the durability of electrocatalysts. [15] DFT calculations on rutile Ru-based oxides indicated that doping of Sr and Ir could expand the Ru lattice and increase the disorder of catalysts, facilitating both the OER activity and stability of as-formed active species (Figure 1d,e). As expected, the optimized Sr 1.7 Ru 5 Ir 1 O 13.7 exhibited an extremely low overpotential at 10 mA cm À2 [h 10 = 190 mV vs.r eversible hydrogen electrode (RHE, all the following mentioned potentials are against RHE)] in acidic media.…”
Section: The Role Of Catalysts and Active Sitesmentioning
confidence: 99%
“…Zhang and Wen prevented the collapse of the crystal structure of Ru-based catalysts by inhibiting the participation of lattice oxygen in the reaction, aiming to improve the stability of Ru-based catalysts. [14] The electronic structure of active Ru sites was modulated by Sr and Ir double modulation strategy, and the ratio of Sr to Ir was optimized according to DFT calculation to achieve the optimal activity and stability (Figure 7a). The prepared SrRuIr oxide catalyst showed an overpotential of only 223 mV at 10 mA cm À 2 for 1,500 h (Figure 7b and c).…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…The obtained SrRuIr oxide OER catalyst realized 1 A cm À 2 at ~1.5 V consistently over 150 h in PEM electrolyzer and exhibited an overpotential of only 223 mV after 1,500 h at 10 mA cm À 2 in three electrodes system. [14] This excellent performance was achieved due to the strong interaction among RuÀ OÀ Ir local structures, which stabilizing the Ru atom and preventing the dissolution of the catalyst. In addition, compared with IrO 2 catalyst, the SrRuIr oxide catalyst avoided the use of a large number of expensive Ir metals and reduced the cost of the catalyst, and this catalyst is expected to achieve further practical applications.…”
Section: Stability and Cost Of Electrocatalystsmentioning
confidence: 99%
See 1 more Smart Citation